The role of public opinion in court decisions on the legality of the death penalty : a look at Uganda and South Africa - Atuguba, Raymond A. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.